2006
DOI: 10.1002/adma.200600213
|View full text |Cite
|
Sign up to set email alerts
|

High‐Density Arrays of Germanium Nanowire Photoresistors

Abstract: Here we present for the first time a study of the photoresistive properties and dynamics of ordered, high-density arrays of germanium nanowire photoresistors. Germanium is a wellknown semiconducting material with an indirect bandgap, E g , of approximately 0.66 eV (temperature T = 300 K) [1] and has been widely used for the fabrication of photodetectors, [2][3][4][5] radiation detectors, [6][7][8] charged particle and photon tracking devices, [9] far-infrared photoresistors, [10] and numerous other devices. [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 28 publications
(28 reference statements)
0
57
0
Order By: Relevance
“…The kinked area possesses longitudinal faults, however, the short dimension of this region indicates that the favourable growth direction is the dominant factor in determining the morphology of this NW. The SAED pattern (Figure 4 (c) inset), taken from the kinked NW, which corresponds to the [1][2][3][4][5][6][7][8][9][10][11] zone axis, shows additional reflections at 1/3{(-224)}-type positions, which are related to the stacking fault content in this kinked NW. As previously noted by Gibson et al 39 for crystalline Si, a 20 complete diamond cubic unit cell having an AaBbCc stacking sequence, produces diffracted amplitude from each pair of layers that are phase shifted by 120°, resulting in exactly zero intensity at the 1/3 (-224)-type position.…”
Section: Kinked Nw Analysismentioning
confidence: 99%
“…The kinked area possesses longitudinal faults, however, the short dimension of this region indicates that the favourable growth direction is the dominant factor in determining the morphology of this NW. The SAED pattern (Figure 4 (c) inset), taken from the kinked NW, which corresponds to the [1][2][3][4][5][6][7][8][9][10][11] zone axis, shows additional reflections at 1/3{(-224)}-type positions, which are related to the stacking fault content in this kinked NW. As previously noted by Gibson et al 39 for crystalline Si, a 20 complete diamond cubic unit cell having an AaBbCc stacking sequence, produces diffracted amplitude from each pair of layers that are phase shifted by 120°, resulting in exactly zero intensity at the 1/3 (-224)-type position.…”
Section: Kinked Nw Analysismentioning
confidence: 99%
“…Although there is a tendency for amorphous deposits to cover the AAO template, the coating can be mechanically removed by polishing to expose MWCNT-encapsulated Ge nanowire arrays which protrude out of the AAO matrix. Past work suggests that it should be possible to exploit these arrays to fabricate gas sensors and optoelectronic devices (Baughman et al, 2002;Agarwal & Lieber, 2006;Polyakov et al, 2006;Erts et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ge has much higher electron and hole mobility than Si (Sze, 1981), which is especially required when electronic devices are scaled down to the sub-100 nm regime. Several growth methods have been developed for the synthesis of Ge nanowires, including laser ablation (Morales & Lieber, 1998;Zhang et al, 2000), thermal evaporation (Gu et al, 2001;Nguyen et al, 2005;Sun et al, 2006;Das et al, 2007;Sutter et al, 2008), supercriticalfluid synthesis (Ryan et al, 2003;Polyakov et al, 2006;Ziegler et al, 2004;Erts et al, 2006), liquid-state synthesis (Heath & LeGoues, 1993;Song et al, 2009), molecular beam epitaxy (Omi & Ogino, 1997), and chemical vapor deposition (CVD) (Kodambaka et al, 2007;Ryan et al, 2003). CVD has been the most widely employed of these synthesis methods, with the aim of synthesizing Ge nanowires in a controllable way via the selection of suitable Ge ordered mesoporous aluminosilicate thin films (Ryan et al, 2003;Ziegler et al, 2004) and AAO membranes Erts et al, 2006) as templates to grow Ge nanowire arrays by the degradation of diphenylgermane (C 12 H 12 Ge) in supercritical CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For most of these studies laser irradiation, with energies between 70-100 W•cm -2 12 , or halogen and tungsten filaments were employed for sample illumination 18,19 . Although heating of the samples due to the high intensity illumination employed was not reported in these studies, Polyakov et al have previously shown that high-powered illumination of Ge nanowires can have a detrimental effect on their photoconductivity by causing exponential thermogenerated current increase inside them 8 . In our study, low-power illumination of 1-4 W•cm -2 was used to study the optoelectronic response of Bi2S3 nanowires as a function of illuminating light photon energy, minimizing any effects due to sample heating and illustrating high optical sensitivity of the nanowires.…”
mentioning
confidence: 90%